2014
DOI: 10.1007/s00374-014-0942-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of inoculum identity in drought stress mitigation by arbuscular mycorrhizal fungi in soybean

Abstract: It is well known that arbuscular mycorrhizal fungi (AMF) effects on plant growth largely depend on fungus identity. The objective of this study was to test whether three individual AMF isolates and their mixture, mitigate drought stress (DS) differentially in soybean (Glycine max) genotype, predicting that under DS, the mixture of the AMF isolates would provide greater benefits to soybean plants than individual ones. In a greenhouse experiment, a drought-susceptible soybean genotype was inoculated with Septogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(44 citation statements)
references
References 44 publications
2
38
1
Order By: Relevance
“…No reduction in leaf chlorophyll content was observed, probably due to the relatively brief exposition to salt stress because of the short growing season. Water stress conditions (25% ETm) exerted highly negative effects on leaf characteristics; in these conditions, AMF inoculation could partially overcome such negative effects, confirming their beneficial role in plant water status under drought stress (Beltrano and Ronco 2008;Grümberg et al 2015) [62,63].…”
Section: Field Experimentsmentioning
confidence: 79%
“…No reduction in leaf chlorophyll content was observed, probably due to the relatively brief exposition to salt stress because of the short growing season. Water stress conditions (25% ETm) exerted highly negative effects on leaf characteristics; in these conditions, AMF inoculation could partially overcome such negative effects, confirming their beneficial role in plant water status under drought stress (Beltrano and Ronco 2008;Grümberg et al 2015) [62,63].…”
Section: Field Experimentsmentioning
confidence: 79%
“…In this study, the AMF phylotypes found in the LY‐2 sample site, especially with respect to the most abundant genus, Septoglomus , must have some traits that allow them to adapt to the specific conditions at this site or to survive as highly adapted spores in the soil. Some studies have demonstrated that Septoglomus was found exclusively under extreme conditions of drought and high temperatures (Bonfim et al, ; Symanczik, Chwat, Boller, Wiemken, & Alyahya'Ei, ) and can play an important role in mitigating drought impact on plants (Grümberg, Urcelay, Shroeder, Vargas‐Gil, & Luna, ). Moreover, the difference in the diversity and community composition of AM fungi under the unhealthy trees in LY‐2, particularly the relatively high frequency of Septoglomus (7.53%), compared to sites LY‐1 (0.99%) and LY‐3 (3.67%), which both contained healthy trees, suggested that the host plants in LY‐2 may allocate different (qualitatively and/or quantitatively) carbon resources to their AM fungal partners (Aguilar‐Trigueros, Powell, Anderson, Antonovics, & Rilling, ), such as specific root‐exudate patterns.…”
Section: Discussionmentioning
confidence: 99%
“…tures (Bonfim et al, 2016;Symanczik, Chwat, Boller, Wiemken, & Alyahya'Ei, 2014) and can play an important role in mitigating drought impact on plants (Grümberg, Urcelay, Shroeder, Vargas-Gil, & Luna, 2015). Moreover, the difference in the diversity and community composition of AM fungi under the unhealthy trees in LY-2, particularly the relatively high frequency of Septoglomus (7.53%), F I G U R E 5 Proportion of total read numbers of operational taxonomic units (OTUs) grouped by arbuscular mycorrhizal fungal (AMF) genus in the root zone of U. chenmoui.…”
Section: Amf Species Diversity In Individual U Chenmoui Root Zonesmentioning
confidence: 99%
“…AMF benefit plants by mediating the availability of important plant nutrients (Smith & Read 2008;Hodge & Storer 2014), promote plant growth and offer protection against drought and soil pathogens (Rodríguez-Echeverría et al 2009;Grümberg et al 2015;Ortiz et al 2015). We examined the AMF community from Cryptostegia madagascariensis root zone, and compared it with the AMF community from Copernicia prunifera root zone.…”
mentioning
confidence: 99%